Microorganism Formulation in Talcum and Molasses for the Organic Waste Biodrying Process - Sukarya Zaenal Arifin; Nisa Rachmania Mubarik; Iman Rusmana (Institut Pertanian Bogor, 2026)
The growing amount of waste needs the employment of ecologically friendly technologies to reduce the likelihood of environmental hazards. Biodrying is a bioenergy processing technique that uses waste to minimize water content while increasing calorific value and temperature, indicating its potential as a renewable energy source. The purpose of this study was to apply a microbial consortia formulation containing talc and molasses to the biodrying process of organic waste, to assess the effect of carrier materials on biodrying performance, and to identify the ideal period for the process. The microbial consortium used included Bacillus thuringiensis SAHA 12.12, Lactiplantibacillus plantarum IN05, Rhizobium sp. RIKG, Saccharomyces cerevisiae L1, Streptomyces sp. A4J, and Trichoderma sp. T2J, all of which were from the IPB Microbiology Laboratory collection. The use of a microbial consortium showed an impact on the measurable results of biodrying organic waste, such as calorific value, water content, and weight reduction. Molasses formulation can boost biodrying efficiency (0.57), calorific value (118−129%), water content (56%), weight loss (34.5%), C/N ratio (32%), and higher temperatures when compared to other carrier materials. Inclusion of talc gives a longer shelf life than molasses. As a result, a molasses-based formulation has the potential to improve biodrying efficiency, while talc can extend the shelf life of the microbial community. Keywords: biodrying, microbial consortium, molasses, organic waste, talc.